Fatherless: Minimnya Keterlibatan Ayah dalam Pengasuhan Anak Remaja Perempuan di Kota Banjarmasin - Fitri, Noor; Damaiyanti, Varinia Pura (Huma: Jurnal Sosiologi, 2025)
Indonesia is known as a fatherless country due to the minimal role of fathers in the daily lives of children, a phenomenon experienced by some adolescent girls in Banjarmasin City. This study aims to determine the involvement of fathers in childcare and the impact of fatherlessness on the behavior of adolescent girls. This research uses a qualitative method with a phenomenological approach. Data collection techniques include frank observation, in-depth interviews, and documentation. Data analysis used the Miles and Huberman model. George Herbert Mead's socialization theory was used as an analytical knife.  The results showed that fatherlessness was caused by parents' divorce or parents' work demands. Some of the perceived forms of fatherlessness include a lack of father's time and attention, physically and verbally violent behavior, and a crisis of children's trust in fathers. The absence of a father figure has a social impact on children's difficulties in building good relationships with peers and increases the risk of engaging in deviant behavioral practices. The lack of protection and affection from a father figure makes children vulnerable to behavioral and emotional disorders.  This research provides a clear and in-depth picture of the fatherless phenomenon and the impact felt by adolescent girls in Banjarmasin City from a sociological point of view. The public needs to be educated about the negative impact of fatherlessness and the importance of fathers in children's development through social media campaigns, seminars, and community activities.